Pengaruh Kecerdasan Emosional Terhadap Prestasi Belajar Matematika Siswa Kelas VII MTsN 1 Wakatobi - Artati Iriana; Armin Armin (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The purpose of this research was to find out the effect of emotional intelligence on mathematics learning uchievement of grade VII students of MTSN I Wakatobi. This research weas an Ex-post Facto reseach. Population in this rescarch was all of grade VII students of MT'sN I Wakatobi consisting 5 classes of 130 students. Sample taken was 40% or 52 students from the total populution, Technique dater collection in this research used questionnaire und documentution. Research outcome showed that: 1) hased om the result of descriptive analysis obtained the level of students' emotional intelligence in general was still in medium category. There were 13.46% students in the ugh category. 67.30% students in the medium category and 19.23% students in low category: 2) the level of students' achievement in general was still in melium category where 17.30% students were in high category, 61.53% students were in medum category and 21.15% were in low category; 3) based on the result of calculation using simple regression obtained linear regression equation Y - 69.320 · 0.0671. It could be concluded that simultaneously there was no effect of emotional mtelligence on learning achievement, it could be seen at F count was 1.037 F table was 4.03. While partially, emotional intelligence has no effect on learning achievement, it could be seen at the value of t count was 1.018 - n table was 2.008.